2021
DOI: 10.1099/acmi.0.000183
|View full text |Cite
|
Sign up to set email alerts
|

Lawsonella clevelandensis is a rare cause of infected chronic contained rupture of abdominal aortic aneurysm

Abstract: Lawsonella clevelandensis is an anaerobic, partially acid-fast, Gram-positive bacillus associated with abscess formation. We present the case of a 70-year-old male with chronic contained rupture of abdominal aortic aneurysm (CCR-AAA) complicated by intra-abdominal abscess formation. An abdominal computed tomography scan revealed a rim-enhancing retroperitoneal collection tracking into the subcutaneous layer of the left flank and buttock, suggestive of CCR-AAA with infec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…L. clevelandensis has been detected in multiple human sources associated with health issues, including dermatitis 20 , various abscesses [21][22][23][24][25] , gut dysbiosis 26 , or vascular graft infection [27][28][29] . Other studies showed that the bacterium can be found in the microbiome of skin 30 , nostrils 31 , human hair follicles 32 , public transit air 33 or even worn spectacles 34 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…L. clevelandensis has been detected in multiple human sources associated with health issues, including dermatitis 20 , various abscesses [21][22][23][24][25] , gut dysbiosis 26 , or vascular graft infection [27][28][29] . Other studies showed that the bacterium can be found in the microbiome of skin 30 , nostrils 31 , human hair follicles 32 , public transit air 33 or even worn spectacles 34 .…”
Section: Discussionmentioning
confidence: 99%
“…22 As such, conventional culture techniques often fail to isolate the bacterium. 28,29 Once successfully cultured, the differentiation of L. clevelandensis from non-tuberculous mycobacteria is still demanding due to its partial acid resistance. 21 Therefore, even if diagnostic microbiology laboratories target the pathogen, culturing, and identification during the routine bacteriological testing period is unlikely.…”
Section: Discussionmentioning
confidence: 99%